Challenging Traditional Islamic Authority: Indonesian Female Ulama and the Fatwa Against Forced Marriages - Arifah Millati Agustina; Nor Ismah (Journal of Islamic Law)
Forced marriage practices have garnered significant attention from various international communities, including the community of female ulama in Indonesia. Despite being a relatively new presence, the community of female ulama affiliated with the Congress of Indonesian Female Ulama (KUPI) has taken a decisive stance against this practice, issuing a firm fatwa (Islamic legal opinion) that underscores its detrimental impact on women. This article addresses the primary question of why female ulama associated with KUPI redefine the concept of wilāyāt al-ijbār (compulsory guardianship) in marriage, departing from the prevailing opinion among traditional Islamic scholars. Through a combination of literature review and field research conducted over eight months, spanning from April to November 2022, this study reveals that KUPI interprets ijbār not as the paternal right to force a daughter into marriage, but rather as a form of guardianship that entails responsibility and nurturance towards their daughter. This fatwa framework is rooted in what is termed the ‘KUPI Trilogy’: ma‘rūf (good), mubādalah (reciprocity), and keadilan hakiki (substantive justice), which promote principles of equality and egalitarianism. By employing theological, sociological, and juridical arguments and emphasizing the experiences of female victims, KUPI contends that the concept of wilāyāt al-ijbār in fiqh (Islamic jurisprudence) is not absolute, thereby prohibiting guardians from coercing or intimidating their daughters into marriage. This article argues that female ulama have boldly contested the authority of traditional ulama by reinterpreting the essence of ijbār in fiqh, while incorporating the lived experiences of female victims of forced marriage practices.